The influence of socio-cultural factors on knowledge-based innovation and the digital economy - Maksim Vlasov; Sergey N. Polbitsyn; Michael Olumekor; Adekunle Oke (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The knowledge economy, fostered by knowledge-based innovation, has been linked to entrepreneurial and economic success, especially in OECD countries. Studies have shown the influence of socio-cultural factors on almost every area of economic behavior. However, few studies have attempted to connect these factors to the knowledge economy. Our research bridges this gap. We investigated the impact of socio-cultural factors on knowledge-based innovation, then we also examined whether digitalization impacted knowledge-based innovation, regardless of the influence of socio-cultural factors. Using official data from Russia's statistical office, we developed a correlation regression model using a linear graphical test and Pearson correlation. Our results show that certain socio-cultural factors significantly influenced knowledge-based innovation. We also found that digitalization could mitigate the negative effects of socio-cultural factors. Digitalization had a positive influence on knowledge-based innovation across all regions and socio-cultural characteristics. Our research provides pioneering analysis of the topic within post-Soviet economies and has huge implications for business practice, policy making, and academic research.
Keywords: 650; digital economy; digitalization; knowledge economy; knowledge-based innovation; regions; socio-culture